Analytic Creep Durability of Rotating Uniform Disks - Yuriy Nyashin; Victor Shishlyaev (International Journal of Rotating Machinery)
Turbine disks of aircraft engines in operation are subjected to alternating thermocyclic deformation under high temperatures. Operation gives rise to sufficiently high stresses and subsequent creep damaging effects.